Agribisnis Jamur Tiram dan Strategi Pengembangannya - Soejono, Djoko; Soetriono, Soetriono; Zahrosa, Dimas Bastara; Maharani, Ariq Dewi; Prabowo, Rachmat Udhi; Amam, Amam (Universitas Galuh, 2024)
The concept of oyster mushroom agribusiness is expected to increase the added value of farmers as business actors. This study aims to review the potential of oyster mushroom agribusiness based on challenges and opportunities. The research was conducted at the Oyster Mushroom Farmers Group (KPJT) Manut, Lumajang Regency. The research data were analyzed by descriptive analysis method, income and value added analysis, and SWOT analysis. The results showed that the oyster mushroom agribusiness concept managed by KPJT Manut, which consisted of 14 people, was able to manage 15,500 baglogs with 12 kinds of processed industrial products. Analysis of the added value of several superior mushroom processed products, namely mushroom meatballs by 45.42%, mushroom sticks by 40.87%, crispy mushrooms by 40.34%, mushroom broth 26.84%, and mushroom ice cream by 14.61%. The main strength factor in the form of collective action is cooperatives, while the main weakness factor is limited creativity and innovation. The main opportunity factor is the need for edutourism for the community, while the main challenge or threat factor is the fluctuation in the selling price of fresh mushrooms.